MANAJEMEN QURANI TAMAN KANAK-KANAK BERBASIS GADGET DALAM PEMBENTUKAN KARAKTER RELIGIUS PESERTA DIDIK - Sari, Windy (Profesi : Jurnal Ilmu Pendidikan dan Keguruan, 2024)
The management of the education of religious character can be carried out by educational institutions. Important character education begins early. Therefore, educational institutions at the kindergarten level are appropriate to strengthen the character education of their students. In its implementation, religious character education requires Quranic management to run optimally. Qur'ani management here is educational management based on the values of the Qur'an, including the values of discipline, synergy, and progress. This research aims to examine school management in shaping children's religious character through the medium of gadgets carried out at school, kindergarten level. A qualitative descriptive approach of the case study type was used in this study. The results showed that kindergarten-level schools can arrange a series of religious activities. This activity is strengthened by school management through the stages of preparing plans, arranging the implementation of activities, and regular evaluation by utilizing gadgets through the digital application "Link Book". School programs run optimally when all elements in the school are actively involved and support these activities